A predictive model of catalytic cracking: Feedstock-induced changes in gasoline and gas composition - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Oreshina A. A. Aleksandra Aleksandrovna; Vymyatnin E. K. Evgeny Konstantinovich (2021, 2021)
Title screen